Constructing Layered MXene/CNTs Composite Film with 2D–3D Sandwich Structure for High Thermoelectric Performance. Issue 23 (14th October 2020) - Ding, Wenjun; Liu, Peng; Bai, Zuzhi; Wang, Yeye; Liu, Guoqiang; Jiang, Qinglin; Jiang, Fengxing; Liu, Peipei; Liu, Congcong; Xu, Jingkun
Abstract: Reasonable heterostructure design can effectively improve the thermoelectric performance of composite materials. High‐conductivity and high‐stability MXenes are expected for the application of thermoelectric conversion benefiting from their diverse electronic properties. In this work, the 2D MXene and 1D SWCNTs are employed to construct layered composite films with 2D–3D sandwich structures in the vertical direction by the wet‐chemical assembly strategy. As a result, sandwich Ti3 C2 T x –SWCNTs–Ti3 C2 T x film shows a higher power factor than that of Ti3 C2 T x /SWCNTs film with interlaced structure, further 25 times higher than that of Ti3 C2 T x film, which mainly due to the considerable electrical conductivity (750.9 S cm −1 ) and enhanced Seebeck (−32.2 µV K −1 ) coefficient. This study provides a feasible and valuable reference for expanding the application field of MXenes‐based materials and reasonably improving their thermoelectric conversion performance. Abstract : Ti3 C2 T x –SWCNTs–Ti3 C2 T x film with a 2D–3D sandwich structure shows a higher power factor, indicating that Mxene as a thermoelectric material has great application potential in the field of thermoelectric conversion.